Riesgo percibido en la construcción en España y Perú: un estudio exploratorio - Rodríguez Garzón, Ignacio (2015)
Introduction: The building sector is one of the most dangerous. It was measured the risk perception possessed by construction workers. Culture can affect risk perception. Objectives: Show the risk perceived by construction workers in Spain and Peru, compare and discuss the similarities and differences between countries. Materials and methods: An exploratory, cross sectional study. Two samples of workers were used: Spanish (N=204) and Peruvian (N=210), obtained in building works, civil works and training centers. The quantification method used is the psychometric paradigm and its adaptation to the Portell & Solé's occupational safety in the NPT of INSHT from Spain. Were used 9 qualitative attributes of risk and a global quantitative attribute. These attributes are measured by Likert scale from 1 to 7 points, while the global quantitative attribute is measured on a scale of 1 to 100. Results: Workers in environments with potential hazards or heavy machinery have a high perception of risk. Workers in both countries considered that have knowledge enough about safety at work. Spanish workers consider their health and safety managers do not have enough knowledge, being better rated in Peru. The probability of incident obtained low score. The global quantitative measure of risk did not obtain statistically significant difference between the two countries. Conclusions: perceived risk in construction should be studied to improve the health of their workers.